PENGARUH PERSEPSI TENTANG KONSELING INDIVIDUAL TERHADAP MINAT BERKONSULTASI KELAS X SMA TARUNA BUMI KHATULISTIWA - Puat, Siti Natijatul; Purwanti, Purwanti; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to reveal the influence of individual counseling perception towards interest in consulting of the studets of X grade of SMA Taruna Bumi Khatulistiwa. Form of this research is a study of corellation. The sample of this research is X grade students. The data collecting technique of this research is indirect communication, which is quastionnaire taht countains 29 questions item on the perseption towards individual counseling variable and 31 questions item on interest of consulting variable. The result of the perception towards individual counseling was only 48,52%, which is categorizad poor. Meanwhile, the interest of consulting was only 31,31%, which is categorizad poor. Based on the result, the contribution of the perception towards individual counseling to the interest of the consulting was 12,74%, which means 87,26% interest of consulting is influenced by other variable that was not found on this research.Â Keyword: Perception Towards Individual Counseling, Interest Of Consulting